FRAMING OF JOURNALISM DISCOURSE TO IMPROVE DISCOURSE COMPETENCE OF SENIOR HIGH SCHOOL STUDENTS - Dadang S. Anshori (University of Kuningan, 2017)
This study aims to describe the analysis model of framing on journalism discourse in Indonesian textbooks in Senior High School to be used in language learning. This research used qualitative method with framing theory from Pan and Kosicki as an tool of analysis. The research data is journalism discourse in textbook amounted to 30 pieces of discourse taken from 10 text books of class X, XI, and XII in Senior High School. The results show the following: (1) The discourse of journalism has received acceptance in the world of education, especially in textbooks. The use of journalism discourse in 10 textbooks is very high and very diverse in terms of number, topic, source, and usage. (2) The journalism discourse in the textbook meets the criteria of reporting value, even if not all reporting value is fulfilled. (3) The frame construction of the journalism discourse in Indonesian textbooks is packaged in different angles according to news topics and facts. (4) The analysis model of journalism discourse framing is developed by focusing on the structural analysis of category, syntax, script, thematic, diction/phrase, and rhetoric.Keywords: construction, discourse, framing, journalism